Sagot :
1. 41xy–18x^2y^2+40
Step-by-step explanation:
Tip: Use The FOIL Method
1.
[tex](4xy)2 - (6xy + 5)(3xy - 8) = 41xy - 18 {x}^{2} {y}^{2} + 40 \\ 2 \times 4xy - (6xy + 5)(3xy - 8) \\ - (6xy + 5)(3xy - 8) \\ 6xy \times 3xy + 6xy( - 8) + 5 \times 3xy + 5( - 8) \\ - (6xy \times 3xy + 6xy( - 8) + 5 \times 3xy + 5( - 8)) \\ 6xy \times 3xy = 18 {x}^{2} {y}^{2} \\ 6xy( - 8) = - 48xy \\ 5 \times 3xy = 15xy \\ 5( - 8) = - 40 \\ 18 {x}^{2} {y}^{2} - 48xy + 15xy - 40 \\ 18 {x}^{2} {y }^{2} - 33xy - 40 \\ - 18 {x}^{2} {y}^{2} + 33xy + 40 \\ 2 \times 4xy - 18 {x}^{2} {y }^{2} + 33xy + 40 \\ 8xy - 18 {x}^{2} {y}^{2} + 33xy + 40 \\ 8xy + 33xy - 18 {x}^{2} {y}^{2} + 40 \\ 8xy + 33xy = 41xy \\ \underline \green{41xy - 18 {x}^{2} {y}^{2} + 40 }[/tex]
[tex] \\ [/tex]
Hope it's help
#CarryOnLearning!